The Relationship Between the Dark Triad Personality Traits, Motivation at Work, and Burnout Among HR Recruitment Workers - Prusik, Monika; Szulawski, Michał (Frontiers in Psychology, 2019)
We focus on the Dark Triad personality traits (Machiavellianism, narcissism, and psychopathy) and their relationships to the mechanisms of motivation and level of burnout that people experience at work. From the motivational perspective, the needs associated with the Dark Triad traits might be satisfied in work environments by selecting different goals or motives. Moreover, the selection of different goals and motives may be related to the level of burnout syndrome that some people develop. We use the Short Dark Triad Personality Test, Barbuto’s Motivation Sources Inventory, and Oldenburg Burnout Inventory to measure triad traits, preferred work motives, and level of burnout, respectively. The results show that in general, some part of the relationship between the Dark Triad traits and burnout is mediated by the motivational sources. As expected, the Dark Triad traits are more closely related to external sources of motivation (especially instrumental motivation), which are in turn partly associated with higher levels of burnout. The results also suggest that the trajectory of the relationship between the Dark Triad traits and burnout via motivation sources is different from expected, presenting a background for discussion.